Pendidikan Karakter Melalui Pembelajaran Algoritma Pemrograman - Dinda Hermaliya; Yahfizham (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2024)
To create a superior generation, every student must receive character education in order to become an individual who is not only intelligent but also has good character. This research aims to find out whether learning programming algorithms has character values ​​that can be adopted by students. This research uses a qualitative research method with a literature study type of research. From the results of the analysis, it can be seen that learning programming algorithms has character values ​​that students can apply in everyday life, where through this learning, students can be trained to think systematically, logically, creatively and also carefully. And of course, by learning programming algorithms, students are required to be able to solve the problems they face.